Secure wireless communication of brain–computer interface and mind control of smart devices enabled by space-time-coding metasurface - Xiao, Qiang; Fan, Lin Han; Ma, Qian; Ning, Yu Ming; Gu, Ze; Chen, Long; Li, Lianlin; You, Jian Wei; Niu, Ya Feng; Cui, Tie Jun (Nature communications, 2025)
Brain–computer interface (BCI) provides an interconnected pathway between the human brain and external devices and paves a potential route for mind manipulations. However, most existing BCI technologies are based on simple signal transmission and are independent of other interface devices, with limited consideration for the reliability and security of the human brain’s information interaction in complicated wireless environments. Here, we propose a deep fusion coding scheme that combines the BCI visual stimulation coding with metasurface space-time coding at the physical layer, enabling reliable and secure information transfers between the human brain and external devices. A brain space-time-coding metasurface platform is designed to implement a secure wireless communication system by using harmonic-encrypted beams. We design and fabricate a proof-of-principle prototype and experimentally show that the proposed wireless BCI scheme can establish a remote but safeguarded paradigm for human–machine interactions and intelligent metasurfaces, providing a potential direction in future secure wireless communications. A brain space-time-coding metasurface platform is proposed by integrating visual stimulation for brain–computer interfaces with dynamic electromagnetic wave manipulations, enabling physical-layer secure wireless communication and mind-driven device control.